Interaction of the Morphogenic Protein RodZ with the Bacillus subtilis Min System - Muchová, Katarína; Chromiková, Zuzana; Valenčíková, Romana; Barák, Imrich (Frontiers in Microbiology, 2018)
Vegetative cell division in Bacillus subtilis takes place precisely at the middle of the cell to ensure that two viable daughter cells are formed. The first event in cell division is the positioning of the FtsZ Z-ring at the correct site. This is controlled by the coordinated action of both negative and positive regulators. The existence of positive regulators has been inferred, but none have presently been identified in B. subtilis. Noc and the Min system belong to negative regulators; Noc prevents division from occurring over the chromosomes, and the Min system inhibits cell division at the poles. Here we report that the morphogenic protein, RodZ, an essential cell shape determinant, is also required for proper septum positioning during vegetative growth. In rodZ mutant cells, the vegetative septum is positioned off center, giving rise to small, round, DNA-containing cells. Searching for the molecular mechanism giving rise to this phenotype led us to discover that RodZ directly interacts with MinJ. We hypothesize that RodZ may aid the Min system in preventing non-medial vegetative division.